GEOGIRA II : Pendekatan ke arah rekabentuk berbantukan komputer - Salleh, Shaharuddin; Rahmat, Hamisan; Sanugi, Bahrom (1992)
The Computer Aided Design (CAD) is a branch of applied mathematics dealing with the study and development of algorithms for the generation of curves and surfaces using computer graphics. Its diverse applications, especially for the generation of geometrical models has brought research activities in thi s area to the forefront. Thi s paper describes an effort to develop a mathematical model using the computer in a project code-named GEOGIRA II. The algorithms used are based on the least squares technique, Hermite and cubic spline interpolations.